Interaction of trace elements in acid mine drainage solution with humic acid - Siripat Suteerapataranon (2018)
The release of metal ions from a coal mining tailing area, Lamphun, Northern Thailand, is studied by leaching tests. Considerable amounts of Mn, Fe, Al, Ni and Co are dissolved in both simulated rain water (pH 4) and 10 mg L-1humic acid (HA) solution (Aldrich humic acid, pH 7). Due to the presence of oxidizing pyrite and sulfide minerals, the pH in both leachates decreases down to ∼3 combined with high sulfate concentrations typical to acid mine drainage (AMD) water composition. Interaction of the acidic leachates upon mixing with ground- and surface water containing natural organic matter is simulated by subsequent dilution (1:100; 1:200; 1:300; 1:500) with a 10 mg L-1HA solution (ionic strength: 10-3mol L-1). Combining asymmetric flow field-flow fractionation (AsFlFFF) with UV/Vis and ICP-MS detection allows for the investigation of metal ion interaction with HA colloid and colloid size evolution. Formation of colloid aggregates is observed by filtration and AsFlFFF depending on the degree of the dilution. While the average HA size is initially found to be {less-than or slanted equal to} 2 nm, metal-HA complexes are always found to be larger. Such observation is attributed to a metal induced HA agglomeration, which is found even at low coverage of HA functional groups with metal ions. Increasing the metal ion to HA ratio, the HA bound metal ions and the HA entities are growing in size from <3 to >450 nm. At high metal ion to HA ratios, precipitation of FeOOH phases and HA agglomeration due to colloid charge neutralization by complete saturation of HA complexing sites are responsible for the fact that most of Fe and Al precipitate and are found in a size fraction > 450 nm. In the more diluted solutions, HA is more relevant as a carrier for metal ion mobilization. © 2006 Elsevier Ltd. All rights reserved.